Implementation of the Power of Two Method to Improve Islamic Manners Learning Outcomes Towards Siblings, Friends and Neighbors at Al Muhajirin Bungaraya Middle School - Yunus; Iwarzah, Yupantri; Yuliani; Yulistianingsih; Yusniawati (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study examines the implementation of The Power of Two method in improving the learning outcomes of Islamic manners towards siblings, friends, and neighbors at Madrasah Tsanawiyah Al Muhajirin Bungaraya. The Power of Two method is a cooperative learning strategy that encourages students to discuss in pairs before sharing their understanding with a larger group. With this approach, students can be more active in understanding and internalizing the values ​​of Islamic manners. This study uses a quantitative approach with an experimental method. Data were obtained through learning outcome tests before and after the application of the method, which were then analyzed using statistical techniques. The results showed a significant increase in students' understanding and attitudes towards the application of Islamic manners in everyday life. Active interactions that occur during the learning process help students strengthen their understanding and improve their social skills. With positive results, this study recommends The Power of Two method as an alternative learning strategy in Islamic Religious Education subjects. This method can be applied more widely to create a more interactive and effective learning atmosphere in shaping students' Islamic character